Protective effects of Theracurmin treatment during experimental infection of the Colombian strain of Trypanosoma cruzi at the testicular site - Pimenta, Breno Luiz; Menezes, Tatiana Prata; Louise, Vitória; Dias, Fernanda Carolina Ribeiro; Machado, Bianca Alves Almeida; Ribeiro, Lais; Pinto, Kelerson Mauro de Castro; Talvani, Andre (Frontiers in Cellular and Infection Microbiology, 2023)
Chagas’ disease is a tropical neglected illness caused by Trypanosoma cruzi and remains one of the most significant causes of morbidity and mortality in South and Central Americas. The disease is caused by a moderate to intense and persistent inflammatory response characterized by local upregulated expression and production of inflammatory mediators that favors the activation and recruitment of distinct cells of the immune system into different tissues to eliminate the parasites. Theracurmin is a curcumin’s derived formulation of nanoparticles. Its anti-inflammatory properties make this bioactive compound a mitigating factor in pathological cases after an overwhelming inflammatory response. Our research focused on the testicular investigation in 28 mice infected by 103 trypomastigote forms of Colombian strain of T. cruzi and preventively treated with Theracurmin. The mice were treated with 30 mg/Kg of Theracurmin during the period of 30 days. At the 30th day post infection animals were euthanized, and its testicles were collected to morphological and immunological assays. The animals infected and treated with Theracurmin presented a reduction in the testicular levels of IL-15 and IL-6. The volume density (%) of the tunica propria was also higher in all infected animals, but Theracurmin decreased this parameter in the treated animals. In the intertubular area, the percentage of some intertubular components was decreased in the infected animals such as the percentage and volume of Leydig cells, connective tissue, and macrophages. Furthermore, our data pointed to the daily use of Theracurmin in the diet as a protective element of the testicular function.